Setup and Control of a Two-Stage Turbocharged Gasoline Engine with Low Pressure EGR in a Prototype Vehicle. Issue 2 (2020) - Keller, Martin; Geiger, Severin; Kluge, Kevin; Günther, Marco; Pischinger, Stefan; Abel, Dirk; Albin, Thivaharan
Abstract: In order to cope with the strict emission standards for vehicles with internal combustion engines, new and innovative air path concepts with e.g. combined turbocharging and exhaust gas recirculation (EGR) are in the focus of research and the industry. Intensive simulative investigations of different concepts usually build the basis for determining which alternatives are promising and should be pursued. The concepts need to be tested and validated under conditions being as realistic as possible. Therefore, engines with the desired air and EGR path layouts are set up on test benches and tested under laboratory conditions. With the real-driving emission (RDE) legislation, it is crucial to test new air path concepts also during real driving on the road. Thus, demonstrator vehicles need to be developed. This paper presents the setup of a prototype demonstrator vehicle with an innovative air path concept for gasoline engines. The engine is equipped with a two stage sequential turbocharging system and a low pressure EGR path. As turbocharged gasoline engines have an increased specific power output, engines can be downsized for increased efficiencies. By using an EGR system, the increased in-cylinder temperatures of turbocharged engines during high load operation can be lowered, reducing the knock tendency and the exhaust gas temperature. The more and more complex air path concepts pose great demands on the process control which needs to handle nonlinear, cross-coupled multiple-input and multiple-output systems with dead times during transient operation. The setup of the vehicle with actuators, sensors and measurement technology as well as a possible control concept will be presented in detail.